Community activity and participation are reduced in transtibial amputee fallers: a wearable technology study. Issue 1 (12th December 2014) - Hordacre, Brenton; Barr, Christopher; Crotty, Maria
Abstract : Wearable technology is an important development in the field of rehabilitation as it has the potential to progress understanding of activity and function in various patient groups. For lower limb amputees, falls occur frequently, and are likely to affect function in the community. Therefore, the purpose of this study was to use wearable technology to assess activity and participation characteristics in the home and various community settings for transtibial amputee fallers and non-fallers. Participants were provided with an accelerometer-based activity monitor and global positioning system (GPS) device to record activity and participation data over a period of seven consecutive days. Data from the accelerometer and GPS were linked to assess community activity and participation. Forty-six transtibial amputees completed the study (79% male, 35% identified as fallers). Participants with a history of falls demonstrated significantly lower levels of community activity (p=0.01) and participation (p=0.02). Specifically, activity levels were reduced for recreational (p=0.01) and commercial roles (p=0.02), while participation was lower for recreational roles (p=0.04). These findings highlight the potential of wearable technology to assist in the understanding of activity and function in rehabilitation and to further emphasise the importance of clinical falls assessments to improve the overall quality of life in this population.